2005
DOI: 10.1038/sj.jcbfm.9600033
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF Reduces Infarct Volume and Improves Functional Outcome after Transient Focal Cerebral Ischemia in Mice

Abstract: Growth factors possess neuroprotective and neurotrophic properties in vitro, but few have been extensively studied in vivo after stroke. In the present study, we investigated the potential functional benefits of granulocyte colony-stimulating factor (G-CSF) administration after focal cerebral ischemia. Male mice underwent 60-minute middle cerebral artery occlusion (MCAO) and received G-CSF (50 lg/kg, subcutaneously) or vehicle (saline) at the onset of reperfusion. Granulocyte colony-stimulating factor-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 55 publications
2
81
2
7
Order By: Relevance
“…Although the administration of G-CSF significantly improved the early neurological outcome, this beneficial effect can be mediated not only by caspase-altering mechanisms but also may involve other mechanisms such as the inhibition of the inflammatory response, as shown previously (Gibson et clearly demonstrated the long-term benefits using the same dose of G-CSF (50μg/kg) on both motor and cognitive outcome up to 3 weeks after an experimental stroke (Gibson et al, 2005a). The dose (Schedule A) used in the present study is a pharmacological dose that has already been shown to cause neuroprotection in previous experimental studies (Gibson et al, 2005b;Gibson et al, 2005a;Schneider et al, 2005). Moreover, this dose is also in the range of G-CSF doses that has been used in human clinical trials (Gabrilove et al, 1988).…”
Section: Discussionmentioning
confidence: 77%
“…Although the administration of G-CSF significantly improved the early neurological outcome, this beneficial effect can be mediated not only by caspase-altering mechanisms but also may involve other mechanisms such as the inhibition of the inflammatory response, as shown previously (Gibson et clearly demonstrated the long-term benefits using the same dose of G-CSF (50μg/kg) on both motor and cognitive outcome up to 3 weeks after an experimental stroke (Gibson et al, 2005a). The dose (Schedule A) used in the present study is a pharmacological dose that has already been shown to cause neuroprotection in previous experimental studies (Gibson et al, 2005b;Gibson et al, 2005a;Schneider et al, 2005). Moreover, this dose is also in the range of G-CSF doses that has been used in human clinical trials (Gabrilove et al, 1988).…”
Section: Discussionmentioning
confidence: 77%
“…Numerous studies have demonstrated G-CSF induced improvements of motor functions after experimental ischemia or other neurological diseases. Interestingly, many of these studies used the rotarod to assess basic motor function (Gibson et al, 2005;Park et al, 2005;Schneider et al, 2005Schneider et al, , 2006. The rotarod is a practicable and easily quantifiable test, in which animals maintain balance on a rotating rod.…”
Section: Discussionmentioning
confidence: 99%
“…Data on vital status was available in 6 studies (Gibson et al, 2005a;Schabitz et al, 2003;Schneider et al, 2005;Sevimli et al, 2009;Six et al, 2003;Yanqing et al, 2006); G-CSF reduced the odds of dying almost 4-fold (OR 0.27, 95% CI 0.14 to 0.51, p<0.0001).…”
Section: Survivalmentioning
confidence: 99%
“…Impairment was measured at various time points post stroke (1, 2, 3, 7, 14, 21 and 35 days); beneficial effects of G-CSF were seen at all times but there was no correlation between reduction in impairment and time to measurement (r s = 0.37, p=0.47). G-CSF increased time that animals stayed on a Rotarod (Gibson et al, 2005a;Lee et al, 2005;Schneider et al, 2006;Sevimli et al, 2009) (table 3) at 1 and 5 weeks post ischaemia. Similarly, improvements were seen in limb function as assessed by limb placement tests at 1 and 4 weeks post stroke.…”
Section: Motor Impairmentmentioning
confidence: 99%
See 1 more Smart Citation